Defining a minimum number of examined lymph nodes improves the prognostic value of lymphadenectomy in pancreas ductal adenocarcinoma. Issue 4 (April 2021) - Pu, Ning; Gao, Shanshan; Beckman, Ross; Ding, Ding; Wright, Michael; Chen, Zhiyao; Zhu, Yayun; Hu, Haijie; Yin, Lingdi; Beckman, Michael; Thompson, Elizabeth; Hruban, Ralph H.; et al.
Abstract: Background: Lymph node (LN) metastasis is associated with decreased survival following resection for pancreatic ductal adenocarcinoma (PDAC). In N0 disease, increasing total evaluated LN (ELN) correlates with improved outcomes suggesting patients may be understaged when LNs are undersampled. We aim to assess the optimal number of examined lymph nodes (ELN) following pancreatectomy. Methods: Data from 1837 patients undergoing surgery were prospectively collected. The binomial probability law was utilized to analyze the minimum number of examined LNs (minELN) and accurately characterize each histopathologic stage. LN ratio (LNR) was compared to American Joint Committee on Cancer (AJCC) guidelines. Results: As ELN total increased, the likelihood of finding node positive disease increased. An evaluation based upon the binomial probability law suggested an optimal minELN of 12 for accurate AJCC N staging. As the number of ELNs increased, the discriminatory capacity of alternative strategies to characterize LN disease exceeded that offered by AJCC N stage. Conclusion: This is the first study dedicated to optimizing histopathologic staging in PDAC using models of minELN informed by the binomial probability law. This study highlights two separate cutoffs for ELNs depending upon prognostic goal and validates that 12 LNs are adequate to determine AJCC N stage for the majority of patients.